Changes in Polypharmacy and Psychotropic Medication Use After Diagnosis of Major Neurocognitive Disorders: A Population-based Study in Québec, Canada. (1st July 2022) - Maltais, Annie; Simard, Marc; Vedel, Isabelle; Sirois, Caroline
Abstract : Background: Older adults with major neurocognitive disorder (MNCD) are often exposed to polypharmacy. We aimed to assess the prescribing and discontinuation patterns of medications following diagnosis of MNCD among community-dwelling older adults. Methods: Using the Quebec Integrated Chronic Disease Surveillance System, we conducted a population-based cohort study comparing 1-year prediagnosis and postdiagnosis use of medications between a group of individuals older than 65 years newly diagnosed with MNCD in 2016-2017 and a control group without MNCD. The difference-in-difference method was used to estimate the prediagnosis and postdiagnosis variation in the number of medications prescribed and in the proportion of psychotropic and anticholinergic medication users. Results: In the MNCD group, the mean number of medications used (excluding Alzheimer disease treatments) increased by 1.25 in the year after the diagnosis. The respective increase was 0.45 in the control group, yielding an adjusted difference-in-differences of 0.81 (95% confidence interval: 0.74; 0.87) between groups. The adjusted difference-in-differences in the proportions of antipsychotic, antidepressant, and anticholinergic medication users was 13.2% (12.5; 13.9), 7.1% (6.5; 7.7), and 3.8% (3.1; 4.6), respectively. Conclusions: The medication burden among older adults tends to increase in the year following a diagnosis of MNCD. The use of antipsychotics and antidepressants may explain a part of the observed increase.